Analysis of User Experience Online Mentoring Platform with User-Centered Design Approach at Giza Design Lab - Ariessaputra, Suthami; Novianung, Lalu Triawanri; Ramadhani, Cipta (DIELEKTRIKA, 2022)
Learning or virtual learning platforms are becoming more and more widespread in education during the COVID-19 epidemic since digital learning eliminates the time and distance barriers. Online learning through internet media is growing rapidly. There are several online learning applications during the pandemic. Giza online mentoring is one of the online platforms based on mentor systems. This study creates a Giza online coaching platform for UX design using the User Centered Design (UCD) methodology. The process included user research to build the empathize, design a prototype, and usability testing of the mentoring platform to validate the solution based on a user-centered approach. The prototype is tested with usability testing. Usability testing is used to evaluate the prototype. Twenty-eight people participated in the initial usability test with a maze design, and the findings showed that 25% of users bounced, 75% of users succeeded indirectly, and 0 individuals succeeded immediately. On the other hand, the second test demonstrates that the improvement results have a respectable impact on user experience, with 82.9 percent user indirect success, 17.1 percent bounce, and 0 users experiencing immediate success.